Sự hình thành kết tụ Carbonat trong trầm tích đầm lầy tại Châu thổ sông Cửu Long - Thuyên, Lê Xuân (Vietnam Journal of Earth Sciences, 2000)
Formation of carbonate concentration inside of salte marsh and lagune sediments on Mekongaetta